2018
DOI: 10.1136/bmjopen-2018-022111
|View full text |Cite
|
Sign up to set email alerts
|

Drug-susceptible tuberculosis treatment success and associated factors in Ethiopia from 2005 to 2017: a systematic review and meta-analysis

Abstract: ObjectivesThe main aim of this study was to assess the overall tuberculosis (TB) treatment success in Ethiopia and to identify potential factors for poor TB treatment outcome.DesignA systematic review and meta-analysis of published literature was conducted. Original studies were identified through a computerised systematic search using PubMed, Google Scholar and Science Direct databases. Heterogeneity across studies was assessed using Cochran’s Q test and I2 statistic. Pooled estimates of treatment success wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 55 publications
4
19
6
1
Order By: Relevance
“…The pooled TSR in the present study is less than the 86% reported in a previous systematic review and meta-analysis of 34 studies in Ethiopia 73. However, one should be cautious in comparing our data with that of Ethiopia due to differences in eligibility criteria.…”
Section: Discussioncontrasting
confidence: 79%
“…The pooled TSR in the present study is less than the 86% reported in a previous systematic review and meta-analysis of 34 studies in Ethiopia 73. However, one should be cautious in comparing our data with that of Ethiopia due to differences in eligibility criteria.…”
Section: Discussioncontrasting
confidence: 79%
“…A study in Europe (2005), reported a pooled estimate of successful outcomes of 74.4% (95% CI 71.0–77.9%), this lower estimate than the one reported in this review could be attributed to the fact that the studies analyzed in this work are prior to 2005 [158]. While, another study in Ethiopia, reported a global success rate of combined TB treatment of 86% (with a 95% CI: 83%-88%), higher than our estimate of successful treatment [159]. To XDR and MDR TB a review published in 2017 reported pooled treatment success of 26% and 60% respectively, which is not different from our results[160].…”
Section: Discussioncontrasting
confidence: 64%
“…between the study settings, difference in sample size and variation of study period. The success rate in the current study was also lower than the pooled estimate of TB treatment success rate in Ethiopia (86%) and WHO 2030 international target of �90% [4,26]. According to this study, age of the patient is one of the significant predictor for unsuccessful treatment outcome.…”
Section: Plos Onecontrasting
confidence: 60%